Clinical and molecular predictors of mortality in neurofibromatosis 2: a UK national analysis of 1192 patients. Issue 10 (14th August 2015) - Hexter, Adam; Jones, Adrian; Joe, Harry; Heap, Laura; Smith, Miriam J; Wallace, Andrew J; Halliday, Dorothy; Parry, Allyson; Taylor, Amy; Raymond, Lucy; Shaw, Adam; Afridi, Shazia; et al.
Abstract : Background: Neurofibromatosis 2 (NF2) is an autosomal-dominant tumour predisposition syndrome characterised by bilateral vestibular schwannomas, considerable morbidity and reduced life expectancy. Although genotype–phenotype correlations are well established in NF2, little is known about effects of mutation type or location within the gene on mortality. Improvements in NF2 diagnosis and management have occurred, but their effect on patient survival is unknown. Methods: We evaluated clinical and molecular predictors of mortality in 1192 patients (771 with known causal mutations) identified through the UK National NF2 Registry. Kaplan–Meier survival and Cox regression analyses were used to evaluate predictors of mortality, with jackknife adjustment of parameter SEs to account for the strong intrafamilial phenotypic correlations that occur in NF2. Results: The study included 241 deaths during 10 995 patient-years of follow-up since diagnosis. Early age at diagnosis and the presence of intracranial meningiomas were associated with increased mortality, and having a mosaic, rather than non-mosaic, NF2 mutation was associated with reduced mortality. Patients with splice-site or missense mutations had lower mortality than patients with truncating mutations (OR 0.459, 95% CI 0.213 to 0.990, and OR 0.196, 95% CI 0.213 to 0.990, respectively). Patients with splice-site mutations in exons 6–15 had lower mortality than patients with splice-site mutations in exons 1–5 (OR 0.333, 95% CI 0.129 to 0.858). The mortality of patients with NF2 diagnosed in more recent decades was lower than that of patients diagnosed earlier. Conclusions: Continuing advances in molecular diagnosis, imaging and treatment of NF2-associated tumours offer hope for even better survival in the future.